Demographic Drivers of Labor Migration and Their Impact on Rural-Urban Development - Mohammad Rizal (Universitas Negeri Semarang, 2025)
Rural-urban labor migration serves as a pivotal driver of local development transformation in developing countries, encapsulating demographic shifts and reshaping economic structures via remittances. This study investigates demographic factors influencing migration patterns in Malang Regency, East Java, Indonesia, and their ramifications for sustainable rural-urban development, emphasizing remittances as a key economic contribution metric. A mixed-methods design was employed, gathering data from migrant workers across five high-migration subdistricts through purposive sampling, with questionnaires facilitating quantitative analysis and in-depth interviews providing qualitative depth. Multinomial logistic regression evaluated settlement intentions, multiple linear regression examined income determinants, and descriptive statistics delineated migrant profiles. Findings reveal that age, education, and marital status exert significant negative effects on settlement intentions, whereas education positively impacts income; factors such as family responsibilities and work tenure proved insignificant. Descriptively, most migrants exhibit no settlement intent, characterized by low education levels, productive ages, and strong origin asset ties, thereby reinforcing circular migration dynamics. These outcomes underscore migration's transient character aimed at enhancing family welfare, highlighting the imperative for policies promoting rural education investments, informal sector formalization, and remittance optimization to cultivate equitable, inclusive development while averting long-term depopulation risks.